Constraints and opportunities for implementing nutrition‐specific, agricultural and market‐based approaches to improve nutrient intake adequacy among infants and young children in two regions of rural Kenya. (17th January 2016) - Hotz, Christine; Pelto, Gretel; Armar‐Klemesu, Margaret; Ferguson, Elaine F.; Chege, Peter; Musinguzi, Enock
Abstract: Several types of interventions can be used to improve nutrient intake adequacy in infant and young child (IYC) diets, including fortified foods, home fortification, nutrition education and behaviour change communication (BCC) in addition to agricultural and market‐based strategies. However, the appropriate selection of interventions depends on the social, cultural, physical and economic context of the population. Derived from two rural Kenyan populations, this analysis combined information from: (1) a quantitative analysis to derive a set of food‐based recommendations (FBRs) to fill nutrient intake gaps in IYC diets and identify 'problem nutrients' for which intake gaps require solutions beyond currently available foods and dietary patterns, and (2) an ethnographic qualitative analysis to identify contextual factors posing opportunities or constraints to implementing the FBRs, including perceptions of cost, convenience, accessibility and appropriateness of the recommended foods for IYC diets and other social or physical factors that determine accessibility of those foods. Opportunities identified included BCC to increase the acceptability and utilisation of green leafy vegetables (GLV) and small fish and agronomic interventions to increase the productivity of GLV and millet. Value chains for millet, beans, GLV, milk and small fish should be studied for opportunities to increase their accessibility in local markets. Processor‐level interventions, such as partially cooked fortified dry porridge mixes or unfortified cereal mixes incorporating millet and beans, may increase the accessibility of foods that provide increased amounts of the problem nutrients. Multi‐sectoral actors and community stakeholders should be engaged to assess the feasibility of implementing these locally appropriate strategies.